Usefulness of Magnetoinertial Wearable Devices in Neurorehabilitation of Children with Cerebral Palsy. (4th September 2018) - Iosa, Marco; de Sanctis, Manuela; Summa, Aurora; Bergamini, Elena; Morelli, Daniela; Vannozzi, Giuseppe
Abstract : Background . Despite the increasing use of wearable magnetoinertial measurement units (MIMUs) for gait analysis, the efficacy of MIMU-based assessment for planning rehabilitation has not been adequately documented yet. Methods . The usefulness of a MIMU-based assessment was evaluated comparing the data acquired by three MIMUs located at the pelvis, sternum, and head levels in 12 children with cerebral palsy (CP, age: 2–9 years) and 12 age-matched children with typical development (TD). Gait stability was quantified in terms of acceleration attenuation coefficients from pelvis to head, pelvis to sternum, and sternum to head. Children with CP were randomly divided in two groups: in the first group (CPI), MIMU-based parameters were used by therapists for planning patient-tailored rehabilitation programs, whereas in the second group (CPB), therapists were blind to the MIMU-based assessment results. Both CPI and CPB were tested before and after the relevant neurorehabilitation program. Ad hoc questionnaires were also administered to therapists of the CPI group to assess the degree of usefulness perceived about the information provided by the MIMU-based assessment. Results . Significant differences were found between children with CP and those with TD for the acceleration attenuation coefficient from pelvis to head (p = 0.048 ) and from pelvis to sternum (p = 0.021 ). After neurorehabilitation, this last parameter increased more in CPI (35%) than in CPB (6%, p = 0.017 for the interaction group per time). The results of the questionnaires showed that therapists agreed with the usability (100% judged it as "easy to use") and usefulness of the MIMU-based assessment in defining patient-oriented interventions (87%). Conclusions . There is a large debate in literature about the efficacy of classical gait analysis that should be enlarged to new technological approaches, such as that based on MIMUs. This study is a first proof of concept about the efficacy of this approach for neurorehabilitation of children with CP.